PELAKSANAAN KEWAJIBAN NEGARA TERHADAP HAM KAUM TRANSGENDER (STUDI TERHADAP PEMENUHAN HAK UNTUK DIPILIH DI INDONESIA) - Wendy Budiati Rakhmi, Rahayu, Elfia Farida (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
The right to be elected is a right that applies to everyone, it means that both men, women and transgender people can use their right to be elected. Transgender basically have the same rights as any other normal human being, witch distinguishes only the will and desire of sexual orientation alone. However, in the implementation the right to be elected transgender often get discriminatory treatment. Based on these discussions. For answering those question, here used social legal approaching with research specification of analytic descriptive. Sort of data contain inside it consisted of primary data, secondary data and tertiary data, whereas the sampling is done through non random sampling method with purposive sampling. Bassed on discussion result that the right to be elected is part of the human rights of every citizen without any distinction between men, women and transgender. The right to be elected is include in derogable right to do that in the implementation of restriction by the state as a stakeholder in the fulfillment of human rights obligations of every citizen. The implementation of the right to be elected has been fulfilled by normative, but legal culture of Indonesian society still hasn’t allowed a transgender use their right to be elected in election to take a position either in public position nor non public position.